The Impact of Electronic Medical Record Implementation on Patient Waiting Time at Outpatient Clinics of Dr. Harjono S. Regional Hospital, Ponorogo - Kusuma Bagus Suseno; Ani Rosita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2025)
The implementation of Electronic Medical Records (EMR) in healthcare facilities is one of the digitalization strategies aimed at improving efficiency and accelerating administrative processes. This study aims to determine the impact of EMR implementation on patient waiting times in several outpatient clinics at Dr. Harjono S. Regional Hospital, Ponorogo. This research employed a descriptive qualitative approach using observation and interviews with staff in five clinics: Orthopedics, Obstetrics and Gynecology, ENT, Psychiatry, and Pediatrics. The analysis focused on comparing patient waiting times before and after the use of EMR. The results show that waiting times for returning patients decreased significantly due to quicker data access. However, waiting times for new patients remained relatively high due to the complexity of the data input process, including the entry of phone numbers and patient identification. Overall, EMR has had a positive impact by speeding up services and simplifying patient data retrieval. Nonetheless, simplifying the data input process for new patients and enhancing operator training remain necessary.